Pengembangan e-LKPD Materi Hidrokarbon Berbasis PBL untuk Melatih Kemampuan Berpikir Kritis : Penelitian - Sari Amelia Anggini; Asrial; Haryanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this study is to determine the conceptual feasibility and procedural feasibility of the e-LKPD developed. This study uses the Lee & Owens development model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The products developed will be validated by material experts and media experts, then assessed by chemistry teachers who are then tested in small groups. The data analysis techniques used in this development are qualitative and quantitative analysis. The results of this study, namely the e-LKPD that was developed, obtained a total score of 4.47 with the category of